High-safety polymer lithium ion battery
By forming a coating of high melting point polymer and flame retardant on the positive and negative electrode sheets of the lithium-ion battery, the internal short circuit and thermal runaway problems that may occur in the extreme environment of the lithium-ion battery are solved, and the safety performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411907829.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-25
AI Technical Summary
Lithium-ion batteries may have internal short circuits under extreme or abnormal environmental conditions, resulting in thermal runaway and safety hazards.
A coating slurry composed of a high melting point polymer and a flame retardant is used to form a cladding layer on both sides of the positive electrode and the negative electrode sheet through in-situ polymerization, thereby improving the safety performance of the battery.
Through the formation of the cladding layer, the flame retardant performance and thermal stability of the lithium-ion battery are improved, the heat diffusion caused by internal short circuit is suppressed, and the safety performance of the battery is significantly improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion batteries, and in particular relates to a high-safety polymer lithium ion battery. Background Art
[0002] Lithium-ion batteries are currently the most widely used energy storage devices, and the rapidly developing electronic products have higher and higher requirements for their energy density and safety performance. When lithium-ion batteries are stored or used for a long time under extreme or abnormal environmental conditions, internal short circuits will occur. As the internal short circuit area expands, the battery releases a large amount of heat in a short period of time, which in turn causes thermal runaway of the battery, posing potential safety hazards to lithium-ion batteries.
[0003] Based on the above safety hazards, the research and development of short-circuit blocking technology for positive and negative electrodes of lithium-ion batteries is extremely important. Flame-retardant materials and flame-retardant technologies can suppress battery thermal runaway to a certain extent, which is also critical for lithium-ion batteries. Polymer electrolytes play an important role in lithium-ion conduction and battery safety, and polymer lithium-ion batteries are also an important direction for the development of lithium-ion batteries. Polymer electrolyte materials can be prepared in situ, which is easy to realize the integrated preparation of lithium-ion batteries and can improve the interface stability of lithium-ion batteries. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a high-safety polymer lithium-ion battery.
[0005] The technical solution adopted by the present invention is: a high-safety polymer lithium-ion battery, including a surface-modified positive electrode plate and a surface-modified negative electrode plate, after coating the coating slurry on both sides of the positive electrode plate, in-situ polymerizing to form a positive electrode coating layer to obtain a surface-modified positive electrode plate, after coating the coating slurry on both sides of the negative electrode plate, in-situ polymerizing to form a negative electrode coating layer to obtain a surface-modified positive electrode plate; wherein the coating slurry includes a high melting point polymer and a flame retardant.
[0006] Preferably, the high melting point polymer is PI and / or PET, and the flame retardant is HPCTP.
[0007] Preferably, the coating slurry includes comonomer 1, comonomer 2, lithium salt, initiator, high melting point polymer, flame retardant and small molecule solvent; the weight percentage of comonomer 1 is 1-10%, the weight percentage of comonomer 2 is 1-10%, the weight percentage of lithium salt is 5-20%, the weight percentage of initiator is 0.01-1%, the weight percentage of high melting point polymer is 5-20%, the weight percentage of flame retardant is 1-10%, and the weight percentage of small molecule solvent is 70-86%.
[0008] Preferably, comonomer one contains hydroxyl groups.
[0009] Preferably, the comonomer 1 is one or more of dipentaerythritol triacrylate, dipentaerythritol tetraacrylate, dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate;
[0010] The second comonomer is at least one of perfluoroalkylethyl acrylate, tetrafluoropropyl methacrylate, hexafluorobutyl methacrylate, 3-methacryloxypropylmethyldimethoxysilane and vinyl-tri(methylethylketoxime)silane;
[0011] The lithium salt is at least one of lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium hexafluorophosphate LiPF6, and lithium tetrafluoroborate LiBF4;
[0012] The initiator is benzoyl peroxide and / or azobisisobutyronitrile;
[0013] The small molecule solvent is at least one of dimethyl carbonate (DMC), nitrogen methyl pyrrolidone (NMP), acetonitrile, tetrahydrofuran, toluene or xylene.
[0014] Preferably, the thickness of a single surface of the positive electrode coating layer or the negative electrode coating layer is 0.5-5 μm.
[0015] A method for preparing a high-safety polymer lithium-ion battery comprises the following steps:
[0016] Step 1: Prepare positive and negative electrodes for lithium-ion batteries;
[0017] Step 2: uniformly mix the raw materials of the coating slurry according to a certain proportion to obtain the coating slurry;
[0018] Step 3: coating the coating slurry on both sides of the positive electrode sheet and the negative electrode sheet respectively, polymerizing and drying in situ to obtain a surface-modified positive electrode sheet and a surface-modified negative electrode sheet;
[0019] Step 4: stack the prepared surface-modified positive electrode sheet and surface-modified negative electrode sheet with the diaphragm, encapsulate, inject in-situ polymerized electrolyte solution to complete the polymer lithium-ion battery assembly, perform in-situ electrolyte polymerization, aging and formation at 40-90°C and 0.3-1.3MPa to complete the integrated preparation of the polymer battery.
[0020] The advantages and positive effects of the present invention are as follows: a high melting point polymer and a flame retardant are coated on the positive electrode sheet and the negative electrode sheet, the flame retardant HPCTP has a flame retardant function, suppresses the combustion reaction inside the lithium ion battery, and improves the safety performance of the polymer lithium ion battery; the high melting point polymer PI or PET component has a higher melting point and flame retardant performance, increases the rupture temperature of the diaphragm when a short circuit occurs in the battery, and suppresses the heat diffusion phenomenon inside the battery;
[0021] By in-situ constructing an electrochemically stable and mechanically stable polymer electrolyte, the polymer battery is prepared in an integrated manner to reduce the interfacial impedance of the polymer battery. DETAILED DESCRIPTION
[0022] The embodiments of the present invention are described below with reference to the accompanying drawings.
[0023] The present invention relates to a high-safety polymer lithium-ion battery, in which the surface of the positive electrode and the negative electrode of the battery are modified, and a coating layer is formed by in-situ polymerization, thereby improving the safety performance of the polymer lithium-ion battery. The coating layer includes a composite material formed by a high melting point polymer and a flame retardant, and a coating slurry including a high melting point polymer and a flame retardant is prepared and coated on both sides of the positive electrode and the negative electrode, respectively, and a battery positive electrode or a battery negative electrode coated on both sides is obtained after in-situ polymerization. Combining it with a diaphragm and an electrochemically stable and mechanically stable polymer electrolyte can reduce the interfacial impedance of the polymer lithium-ion battery, and further improve the stability and safety performance of the polymer lithium-ion battery system.
[0024] Among them, the high melting point polymer used is PI and / or PET, the flame retardant used is hexaphenoxy cyclotriphosphazene (HPCTP), and in addition, the coating slurry also includes two comonomers, which can form a cross-linked polymer network structure, one of which contains hydroxyl groups, and forms hydrogen bonds with PI and / or PET and HPCTP materials to improve the stability of the polymer structure and battery system. Specifically, the coating slurry includes comonomer 1, comonomer 2, lithium salt, initiator, high melting point polymer, flame retardant and small molecule solvent. The weight percentage of comonomer 1 is 1-10%, the weight percentage of comonomer 2 is 1-10%, the weight percentage of lithium salt is 5-20%, the weight percentage of initiator is 0.01-1%, the weight percentage of high melting point polymer is 5-20%, the weight percentage of flame retardant is 1-10%, and the weight percentage of small molecule solvent is 70-86%.
[0025] The first comonomer is one or more of dipentaerythritol triacrylate, dipentaerythritol tetraacrylate, dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate; the second comonomer is at least one of organic compounds such as perfluoroalkylethyl acrylate, tetrafluoropropyl methacrylate, hexafluorobutyl methacrylate, 3-methacryloxypropylmethyldimethoxysilane and vinyl-tri(methylethylketoxime)silane; the lithium salt is at least one of lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium hexafluorophosphate LiPF6 and lithium tetrafluoroborate LiBF4; the initiator is one or two of benzoyl peroxide and azobisisobutyronitrile; the small molecule solvent is at least one of dimethyl carbonate (DMC), nitrogen methyl pyrrolidone (NMP), acetonitrile, tetrahydrofuran, toluene or xylene.
[0026] The specific preparation method of high-safety polymer lithium-ion battery is as follows:
[0027] Step 1: Prepare positive electrode and negative electrode of lithium-ion battery;
[0028] Step 2: preparing a coating slurry, mixing comonomer 1, comonomer 2, lithium salt, initiator, high melting point polymer, flame retardant and small molecule solvent in proportion to obtain a coating slurry;
[0029] Step 3: coating the coating slurry on both sides of the positive electrode sheet and the negative electrode sheet, polymerizing and drying in situ to obtain a surface-modified positive electrode sheet and a surface-modified negative electrode sheet;
[0030] Step 4: stack the prepared surface-modified positive electrode sheet and surface-modified negative electrode sheet with the diaphragm, encapsulate, inject the in-situ polymerized electrolyte solution, and complete the polymer lithium-ion battery assembly, perform in-situ electrolyte polymerization, aging and formation at 40-90°C and 0.3-1.3MPa to complete the integrated preparation of the polymer battery.
[0031] The surface modified positive electrode sheet and surface modified negative electrode sheet are positive electrode sheets and negative electrode sheets coated with high melting point polymers and flame retardants. HPCTP has flame retardant function, which inhibits the combustion reaction inside the lithium-ion battery and improves the safety performance of the polymer lithium-ion battery. The PI or PET components have high melting points and flame retardant properties, which increase the rupture temperature of the diaphragm when a short circuit occurs in the battery and inhibit the thermal diffusion phenomenon inside the battery. At least one of the copolymers contains hydroxyl groups, which form hydrogen bonds with the PI / PET / HPCTP materials in the positive and negative electrode materials to improve the stability of the polymer structure and the battery system. By in-situ constructing an electrochemically stable and mechanically stable polymer electrolyte, the polymer battery is prepared in an integrated manner to reduce the interface impedance of the polymer battery.
[0032] A high melting point polymer PI is used, which contains an imide ring (-CO-NR-CO-) on the main chain. Its rigid aromatic heterocyclic structure is one of the polymer materials with the best heat resistance at present, and PI has excellent electrochemical stability. In addition, a high melting point polymer PET is also used. PET contains ester bonds and has good heat resistance, organic solvent resistance and antioxidant properties. HPCTP is used as the flame retardant in the coating slurry. HPCTP has good thermal stability and flame retardant properties. Its unique PN structure can easily form a synergistic system with other polymers, and it also has excellent toughening and other modification functions for polymer materials. It has excellent water resistance, oxidation resistance, thermal stability and molding processability. The combination of PI / PET and HPCTP in composite materials can have rich functional groups, and can form strong intermolecular forces by using hydrogen bonds, aromatic ring stacking and other synergistic effects, so that the composite material can have better structural stability.
[0033] The scheme of the present invention is described below in conjunction with the accompanying drawings, wherein the experimental methods without specific operating steps are all carried out in accordance with the corresponding product instructions, and the instruments, reagents, and consumables used in the examples can all be purchased from commercial companies unless otherwise specified.
[0034] Embodiment 1:
[0035] 1.1 Preparation of positive and negative electrodes for lithium-ion batteries
[0036] The positive and negative electrode sheets were prepared by conventional methods. The positive electrode formula included NCM622, CNT and PVDF in a mass ratio of 97.4:1.2:1.4; the negative electrode formula included graphite / SiOx (8 / 2), conductive carbon black and polyimide in a mass ratio of 96.7:0.7:2.6.
[0037] 1.2 Preparation of positive and negative electrode coating slurry
[0038] The coating slurry includes dipentaerythritol tetraacrylate, 3-methacryloxypropylmethyldimethoxysilane, LiTFSI, azobisisobutyronitrile, PI, HPCTP, toluene and NMP, wherein the weight percentage of each component is 1%, 3%, 12%, 0.05%, 6%, 2%, 20% and 55.95% in sequence. The components are mixed according to the proportion and stirred evenly to form the coating slurry.
[0039] 1.3 Preparation of surface modified positive electrode sheet and surface modified negative electrode sheet
[0040] Apply the coating slurry on both sides of the positive and negative electrodes, and control the coating amount on one side to 0.2 mg / cm 2 , treated at 45°C for 2h under anaerobic conditions, polymerized in situ and fully dried to obtain composite positive and negative electrodes for lithium-ion batteries.
[0041] 1.4 Preparation of in-situ polymerized electrolyte solution
[0042] The in-situ polymerized electrolyte includes dipentaerythritol hexaacrylate, ECA, azobisisobutyronitrile, EMC, DEC, EC, PC, FEC, VC, PS and LiFSI, and the mixing mass ratio is 0.9%: 2%: 0.1%: 22%: 20%: 20%: 10%: 6%: 2%: 2%: 15%. The raw materials are added in proportion and mixed evenly for standby use.
[0043] 1.5 Integrated preparation of polymer lithium-ion batteries
[0044] The prepared composite positive electrode sheet and composite negative electrode sheet are stacked with a separator (double-sided ceramic coating, 16μm+2μm+2μm), injected with an in-situ polymerized electrolyte solution, and assembled into a polymer lithium-ion battery according to conventional technical methods. The electrolyte is in-situ polymerized, aged and formed at 60°C and 0.8MPa to complete the integrated preparation of the polymer battery.
[0045] Embodiment 2:
[0046] 2.1 Preparation of modified positive and negative electrodes for lithium-ion batteries
[0047] The positive and negative electrode sheets were prepared by conventional methods. The positive electrode formula included NCM622, CNT and PVDF in a mass ratio of 97.4:1.2:1.4; the negative electrode formula included graphite / SiOx (8 / 2), conductive carbon black and polyimide in a mass ratio of 96.7:0.7:2.6.
[0048] 2.2 Preparation of positive and negative electrode coating slurry
[0049] The coating slurry includes dipentaerythritol pentaacrylate, 3-methacryloxypropylmethyldimethoxysilane, LiPF6, azobisisobutyronitrile, PI, PET, HPCTP, toluene and NMP, wherein the weight percentage of each component is 1%, 3%, 12%, 0.05%, 4%, 2%, 2%, 20% and 55.95% in sequence. The components are mixed according to the proportion and stirred evenly to form the coating slurry.
[0050] 2.3 Preparation of surface-modified positive electrode sheets and surface-modified negative electrode sheets
[0051] Apply the coating slurry on both sides of the positive and negative electrodes, and control the coating amount on one side to 0.2 mg / cm 2 , treated at 45°C for 2h under anaerobic conditions to enable in-situ polymerization and sufficient drying to obtain composite positive and negative electrodes for lithium-ion batteries.
[0052] 2.4 Preparation of in-situ polymerized electrolyte solution
[0053] The in-situ polymerized electrolyte includes dipentaerythritol hexaacrylate, ECA, azobisisobutyronitrile, EMC, DEC, EC, PC, FEC, VC, PS and LiFSI, and the mixing mass ratio is 0.9%: 2%: 0.1%: 22%: 20%: 20%: 10%: 6%: 2%: 2%: 15%. The raw materials are added in proportion and mixed evenly for standby use.
[0054] 2.5 Integrated preparation of polymer lithium-ion batteries
[0055] The composite positive electrode sheet, composite negative electrode sheet, and separator (double-sided ceramic coating, 16μm+2μm+2μm) are stacked, injected with in-situ polymerized electrolyte solution, and the polymer lithium-ion battery is assembled according to conventional technical methods. The electrolyte is in-situ polymerized, aged and formed at 60°C and 0.8MPa to complete the integrated preparation of the polymer battery.
[0056] Comparative Example:
[0057] The positive and negative electrodes of the lithium-ion battery and the in-situ polymerized electrolyte solution were prepared according to the method of Example 1 or 2. The difference from Examples 1 and 2 is that the positive and negative electrodes of the lithium-ion battery were not surface modified, but were directly assembled with the in-situ polymerized electrolyte solution to form a lithium-ion battery. After formation, a comparison lithium-ion battery was obtained.
[0058] The battery is charged at 0.33C until it reaches 4.4V and then cut off at 0.05C. The steel needles were subjected to acupuncture safety tests, and the results are shown in Table 1.
[0059] Table 1 Soft pack battery safety test results of the embodiment
[0060] Soft pack battery model capacity energy Fully charged battery acupuncture Example 1 INP1188194 38Ah 330Wh / kg All 3 passed Example 2 INP1188194 38Ah 330Wh / kg All 3 passed Comparative Example INP1188194 38Ah 330Wh / kg 3 through 1
[0061] It can be seen from the data in Table 1 that the batteries prepared in the embodiment and the comparative example are the same in capacity and energy, but in the needle puncture test, the batteries prepared in the embodiment all passed, while the conventional lithium-ion batteries failed the test; the surface modification of the positive and negative electrodes of the battery by this method will not affect the performance of the battery itself, and can significantly improve the safety of the battery.
[0062] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A high-safety polymer lithium-ion battery, characterized in that: The invention comprises a surface-modified positive electrode plate and a surface-modified negative electrode plate. The coating slurry is coated on both sides of the positive electrode plate and then polymerized in situ to form a positive electrode coating layer to obtain a surface-modified positive electrode plate. The coating slurry is coated on both sides of the negative electrode plate and then polymerized in situ to form a negative electrode coating layer to obtain a surface-modified positive electrode plate. The coating slurry comprises a high melting point polymer and a flame retardant.
2. The high-safety polymer lithium-ion battery according to claim 1, characterized in that: The high melting point polymer is PI and / or PET, and the flame retardant is HPCTP.
3. The high-safety polymer lithium-ion battery according to claim 2, characterized in that: The coating slurry includes comonomer 1, comonomer 2, lithium salt, initiator, high melting point polymer, flame retardant and small molecule solvent; the weight percentage of comonomer 1 is 1-10%, the weight percentage of comonomer 2 is 1-10%, the weight percentage of lithium salt is 5-20%, the weight percentage of initiator is 0.01-1%, the weight percentage of high melting point polymer is 5-20%, the weight percentage of flame retardant is 1-10%, and the weight percentage of small molecule solvent is 70-86%.
4. The high-safety polymer lithium-ion battery according to claim 3, characterized in that: Comonomer 1 contains hydroxyl groups.
5. The high-safety polymer lithium-ion battery according to claim 3, characterized in that: The first comonomer is one or more of dipentaerythritol triacrylate, dipentaerythritol tetraacrylate, dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate; The second comonomer is at least one of perfluoroalkylethyl acrylate, tetrafluoropropyl methacrylate, hexafluorobutyl methacrylate, 3-methacryloxypropylmethyldimethoxysilane and vinyl-tri(methylethylketoxime)silane; The lithium salt is at least one of lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium hexafluorophosphate LiPF6, and lithium tetrafluoroborate LiBF4; The initiator is benzoyl peroxide and / or azobisisobutyronitrile; The small molecule solvent is at least one of dimethyl carbonate (DMC), nitrogen methyl pyrrolidone (NMP), acetonitrile, tetrahydrofuran, toluene or xylene.
6. The high-safety polymer lithium-ion battery according to claim 1, characterized in that: The thickness of a single surface of the positive electrode coating layer or the negative electrode coating layer is 0.5-5 μm.
7. A method for preparing a high-safety polymer lithium-ion battery according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: Step 1: Prepare positive and negative electrodes for lithium-ion batteries; Step 2: uniformly mix the raw materials of the coating slurry according to a certain proportion to obtain the coating slurry; Step 3: coating the coating slurry on both sides of the positive electrode sheet and the negative electrode sheet respectively, polymerizing and drying in situ to obtain a surface-modified positive electrode sheet and a surface-modified negative electrode sheet; Step 4: stack the prepared surface-modified positive electrode sheet and surface-modified negative electrode sheet with the diaphragm, encapsulate, inject in-situ polymerized electrolyte solution to complete the polymer lithium-ion battery assembly, perform in-situ electrolyte polymerization, aging and formation at 40-90°C and 0.3-1.3MPa to complete the integrated preparation of the polymer battery.
Citation Information
Patent Citations
Current collector and preparation method thereof, electrode plate, secondary battery and electric device
CN115810760A
Preparation method of double-layer all-solid-state high-performance electrolyte
CN117810546A
Conductive agent for lithium ion battery as well as preparation method and application of conductive agent
CN118572111A
Cited By
High-safety flexible pole piece, preparation method and flexible lithium ion battery
CN121565789A